2015
DOI: 10.1021/acs.organomet.5b00561
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Hydroalkoxylation of Terminal Alkynes Catalyzed by a Dipyrrinato Rhodium(I) Complex with Unusual Selectivity

Abstract: An operationally simple and atom-economical method for the E-selective preparation of enol ethers is described. A novel dicarbonyl(5-phenyldipyrrinato)rhodium complex, 2, was prepared in four synthetic steps, characterized by X-ray crystallography and NMR spectroscopy, and then investigated as a catalyst for the intermolecular hydroalkoxylation of terminal alkynes. Solvent and substrate studies were used to gain insight into the mechanism of the reaction. Cyclic voltammetry was also used to investigate the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The endo/exo-dig cyclic products are accessed throughi ntramolecular heteroannulations (Scheme 1). [11] Computational studies by Wang and co-workersr evealed that the 8-quinolinolato oxygen atom facilitated alcohold eprotonation to am ore potent On ucleophile, which readily added to the Rh-vinylidene followed by protont ransfers. [3] Enol ethers are important functionalities in organic synthesis and are used widely in cross-coupling,r ing-closing metathesis, and cycloaddition reactions and for the synthesis of pharmaceuticals.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The endo/exo-dig cyclic products are accessed throughi ntramolecular heteroannulations (Scheme 1). [11] Computational studies by Wang and co-workersr evealed that the 8-quinolinolato oxygen atom facilitated alcohold eprotonation to am ore potent On ucleophile, which readily added to the Rh-vinylidene followed by protont ransfers. [3] Enol ethers are important functionalities in organic synthesis and are used widely in cross-coupling,r ing-closing metathesis, and cycloaddition reactions and for the synthesis of pharmaceuticals.…”
mentioning
confidence: 99%
“…[2] However,addition reactions of weak nucleophiles such as water and alcohol remain achallenging task. [11] Computational studies by Wang and co-workersr evealed that the 8-quinolinolato oxygen atom facilitated alcohold eprotonation to am ore potent On ucleophile, which readily added to the Rh-vinylidene followed by protont ransfers. [4] Whereasmetal-catalyzed intramolecular hydroalkox-ylationsa re well reported, [5] intermolecular reactions between alcohols and alkynes are difficult [6] and often demandt he use of as trong base or harsh conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…19a) active for the catalytic hydroalkoxylation of phenylacetylene and MeOH. 126 The reaction with 1 mol% of 61 in N,Ndimethylacetamide (DMA) proceeded with a conversion of 98% and a clear preference for the E product. Interestingly, the substrate scope was found to be wide, since neither electron-donating nor electron-withdrawing group in the para position of the aromatic unit of the substrate impacted negatively the conversion rate.…”
Section: Rh(i)/rh(iii)-based Catalystsmentioning
confidence: 99%
“…Recently, Messerle and coworkers demonstrated that the dipyrrinato‐ligated rhodium (I) complex ( 2cat ) could also catalyze the same type of hydroalkoxylations but afforded ( E )‐enol ethers [e.g. Equation ] . When compared, the two catalytic systems were identical except for the ligands but gave products with different configurations.…”
Section: Introductionmentioning
confidence: 99%